INTERVENSI EDUKASI SINGKAT TENTANG ATRESIA BILIER PADA TENAGA KESEHATAN: BUKTI PENINGKATAN PENGETAHUAN DAN KESIAPAN SKRINING DENGAN KARTU WARNA TINJA - Bagus Setyoboedi; Rendi Aji Prihaningtyas; Yovani Savitri; Martono Tri Utomo; Sjamsul Arief (Jurnal Abdi Insani, 2025)
Biliary atresia is the most common cause of neonatal cholestasis, characterized by prolonged jaundice, pale stools, and dark-colored urine. Early detection is crucial to prevent further liver damage. However, delayed diagnosis is still frequently encountered, mainly due to the lack of healthcare providers’ knowledge in recognizing the early signs of biliary atresia. This study aimed to determine the significance of a targeted health education intervention in improving knowledge of early detection of biliary atresia among healthcare providers. A quasi-experimental study was conducted at Padangan District General Hospital, Bojonegoro, East Java, using a pre-test/post-test questionnaire design. The health intervention consisted of education on biliary atresia and the introduction of the stool color card as an early detection tool, delivered by a Pediatric gastroenterologist and hepatologist. The Wilcoxon signed-rank test was performed with a significance level of p<0.05.A total of 101 respondents participated, predominantly female (88.1%), with the largest age group being 30–39 years (37.6%). Most respondents had more than five years of work experience (81.2%). The mean knowledge score significantly increased from 86.3 in the pre-test to 93.2 in the post-test (p < 0.001). Prior to the intervention, only 12.9% of respondents scored <70, whereas after the intervention nearly all participants (98%) scored >70. Knowledge regarding early symptoms of biliary atresia, the risks of delayed diagnosis, and the use of the Stool Color Card showed meaningful improvement on early detection of biliary atresia. A health education intervention is effective in improving healthcare providers’ knowledge of early detection of biliary atresia.